Interactions between hyperbolic geometry, quantum topology and number theory : Workshop June 3-13, 2009, Conference June 15-19, 2009, Columbia University, New York, NY - Workshop on Interactions between Hyperbolic Geometry, Quantum Topology and Number Theory; Champanerkar, Abhijit (Contemporary mathematics, 2011)
This book is based on a 10-day workshop given by leading experts in hyperbolic geometry, quantum topology and number theory, in June 2009 at Columbia University. Each speaker gave a minicourse consisting of three or four lectures aimed at graduate students and recent PhDs. The proceedings of this enormously successful workshop can serve as an introduction to this active research area in a way that is expository and broadly accessible to graduate students.